HESIOD IN MACEDONIAN CULTURAL ENVIRONMENT (Philological Studies, 2019)
The survey of Hesiod’s literary reception in the Macedonian cultural environment is a complex literary communication process that can be followed in several receptive phases (passive, indirect, reproductive) on several levels (intertemporal, interlingvistic and intercultural level). The beginnings of Hesiod’s reception in the Macedonian cultural environment are evident in the XIX century according to contacts of Macedonian teachers Grigor Prličev and Jordan Hadži Konstantinov-Džinot with the epic works of Hesiod in one of the classical languages. This phase is considered passive. Later, in the first half of XX century, the presence of the works of Hesiod as translations in some of the neighboring languages allows us to speak about indirect channels of literary reception. The announcement of the first reviews of Hesiod’s works in Macedonian periodicals from the second half of the XX century and the emergence of the first Macedonian translations of Works and Days (1996) and Theogony (2001) at the end of the past century, marks the reproductive phase of Hesiod’s literary reception in the Macedonian cultural environment. Analysis of the beginning, the scope, the content and the character of Hesiod’s literary reception evoked a number of issues, such as the meetings of the classical work with readers in other eras (intertemporal level), the trust of literary translation (interlingvistic level), and more specific, the literary, aesthetic and ideological meetings of Macedonian culture with the ancient Hellenic culture (intercultural level).
Keywords: Hesiod, Ancient epic, reception, Theogony, Works and Days, intercultural liaison, literary liaison